sandeep211986 wrote:

reachskishore wrote:

Stem : x^2 - y^2 = (x+y)(x-y)

S1 : 2xy = x+y Not Sufficient

S2 : x^2y-xy^2 = 1 ---> xy(x-y) = 1.

So both, xy = (x-y) = 1. Again Not sufficient.

S1 + S2 = as xy = 1, x+y = 2xy = 2(1) = 2 ---> x+y = 2

and x-y = 1. So (x+y)(x-y) = 2*1 = 2.

Hence C is the answer

From statement 2: xy(x-y) = 1.Then why can't be xy = 2 and x-y be 1/2 or vice versa or any other combination (such as 1/3 and 3 etc. ) so that there product is 1.

I suppose the answer should be E.

Experts please advice.

Hi Sandeep,

Nice catch there. I never thought about that scenario. But, on a second note, the answer remains same as per your data.

We have xy(x-y) = 1. So, going by your data. Say xy = a and (x-y) = 1/a

so (x+y) = 2xy = 2a.

Now (x+y)(x-y_ = 2 * a * 1/a ---> a and 1/a cancels out and 2 remains.

Alternatively if you consider xy = 1/a and (x-y) = a , then too, 2 remains to be the answer.